Trasplantes de progenitores hematopoyéticos - Alfaro L., Jorge; González G., Néstor (Revista Hospital Clínico Universidad de Chile, 2008)
The stem cell transplantation (SCT) has improved the disease free survival of a great number of diseases. It began as an experimental procedure, used as last resource in terminally ill patients. Nowadays it is a proved tool that allow the patient receive high dose of chemoradiotherapy, without the bone marrow toxicity being a conditioning step. The haematological recovery follows the same mechanisms that the organisms have designed for this purpose. First, cryopreservation of progenitors stem cells (PSCs) is required, then these cells are re-infused into the blood. The PSCs find their own homing in the bone marrow, proliferate, differentiate andre establish the haematopoietic balance. The present revision gives some information about the different phase or a SCT, physiology background, indications and principals adverse effects.